Facies and sedimentology of a carbonate delta drift (Miocene, Maldives). Issue 4 (29th April 2019) - Reolid, Jesús; Betzler, Christian; Lüdmann, Thomas
Abstract: The identification of sediment drifts typically relies on interpretation of reflection seismic data sets. This study sedimentologically analyzed an example of a carbonate delta drift previously identified in seismics in order to provide a catalogue of characteristic features at core and seismic scale for allowing testing the occurrence of this poorly known type of deposit elsewhere. Cores and downhole logs recovered during International Ocean Discovery Program Expedition 359 to the Maldives, in combination with seismic data, were analyzed with this objective. The diagnostic criteria for the sedimentological recognition of a delta drift are: (i) the development of sigmoidal clinoforms that thin out towards proximal and distal settings; (ii) a proximal part characterized by coarse‐grained facies with abundant shallow‐water components and distal areas dominated by fine‐grained facies with rare to absent shallow‐water components; (iii) winnowing of the finer fraction in proximal facies; (iv) extensive fragmentation of most of the bioclasts with minor intervals of well‐preserved components; (v) bigradational intervals in the proximal part and large channels in proximal to distal settings; and (vi) the lobe to delta shaped outline of the sediment accumulation. The characteristic shallow‐water fossil assemblage of the Mid to Upper Miocene delta drift consists of large benthic foraminifera ( Amphistegina, Cycloclypeus, Lepidocyclina, Operculina and Heterostegina ), fragmented red algae and bryozoans, equinoid debris, and Halimeda plates. The deeper‐water part of the drift bodies consists of fine‐grained planktonic foraminifera‐rich wackestone. Condensed intervals may occur as result of enhanced bottom‐current activity. In contrast to siliciclastic drift bodies, the carbonate delta drift has an important contribution by in situ shallow‐water carbonate production reminiscent of a shoal. In situ carbonate production is proposed as a major controlling factor which is as important as the pelagic settling or the shaping by density and bottom currents in siliciclastic drifts. In the absence of three‐dimensional data and in two‐dimensional views the carbonate delta drift sediment bodies resemble carbonate ramps, which indicates that there may be the need to re‐evaluate various cases of such systems described from the geological record.